2021
DOI: 10.1038/s41598-021-83363-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and heavy metal removal efficiency of nickel ferrite nanoparticles (NFN’s)

Abstract: The heavy metals, such as Cr(VI), Pb(II) and Cd(II), in aqueous solutions are toxic even at trace levels and have caused adverse health impacts on human beings. Hence the removal of these heavy metals from the aqueous environment is important to protect biodiversity, hydrosphere ecosystems, and human beings. In this study, magnetic Nickel-Ferrite Nanoparticles (NFNs) were synthesized by co-precipitation method and characterized using X-Ray Diffraction (XRD), Energy Dispersive Spectroscopy (EDS) and Field Emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Narayana et al reported an optimized lead ions Pb (II) removal by a nanocomposite of inverse spinel nickel ferrite and reduced graphene oxide (Narayana et al 2022). Their results showed that the prepared sample could obtain a The removal of different heavy metals such as Cr (VI), Cd (II), and Pb (II) from wastewater was also reported by Khoso et al using magnetic Nickel-Ferrite Nanoparticles (NFNs) prepared by a co-precipitation method (Khoso et al 2021). They also studied the effect of many parameters, including pH, dose, and contact time, on the adsorption efficiency.…”
Section: Heavy Metal Removal Applicationsmentioning
confidence: 60%
“…Narayana et al reported an optimized lead ions Pb (II) removal by a nanocomposite of inverse spinel nickel ferrite and reduced graphene oxide (Narayana et al 2022). Their results showed that the prepared sample could obtain a The removal of different heavy metals such as Cr (VI), Cd (II), and Pb (II) from wastewater was also reported by Khoso et al using magnetic Nickel-Ferrite Nanoparticles (NFNs) prepared by a co-precipitation method (Khoso et al 2021). They also studied the effect of many parameters, including pH, dose, and contact time, on the adsorption efficiency.…”
Section: Heavy Metal Removal Applicationsmentioning
confidence: 60%
“…Besides the stabilization of spinel ferrites nanoparticles, these functional groups enhance the selectivity in aqueous solution by hyper-branching, ionic or electrostatic interactions. Many isotherms as well as kinetic models are utilized to verify the adsorption potential of various spinel ferrites nanoparticles and their composites [46]. Mainly most frequently utilized models for isotherm are Langmuir and Freundlich isotherm models and for kinetics pseudo first and pseudo second order kinetic models.…”
Section: Spinel Ferrites Nanoparticles and Composites Used For Wastewater Remediationmentioning
confidence: 99%
“…The aforementioned factors (Fig. 6) have already been well studied in regards to adsorption and removal of contaminants [30,46].…”
Section: Factors Affecting the Adsorption Ability Of Spinel Ferrite Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used as a low-cost renewable source for producing activated carbon by burning the litter to at least 700 o C resulting in the formation of a lattice-like carbon particle structure. Activated carbon is used for the adsorption of contaminants in wastewater [10,11], along with this several physico chemical and hydroponic techniques have been reported for metals removal [12][13][14].…”
Section: Introductionmentioning
confidence: 99%